2018
DOI: 10.1016/j.fuel.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from batch and continuous oleic acid esterification using zeolite catalysts

Abstract: The esterification of oleic acid with ethanol was studied in both batch and continuous conditions in a fixed-bed reactor over FAU-type zeolites prepared from shale rock. The addition of Co-Ni-Pt to the zeolite increased the catalyst activity over the entire reaction temperature range. Experiments confirmed that esterification follows pseudo first-order kinetics. Thermodynamic analysis and Thiele modulus calculations show that the reaction is kinetically controlled in batch conditions, while diffusional limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Similar immobilized enzyme activity decreased in polar solvents can also be found in many reactions. [30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…Similar immobilized enzyme activity decreased in polar solvents can also be found in many reactions. [30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…After 60 min, the oleic acid conversion in the presence of synthesized zeolite from kaolin was about 85%, while the corresponding amount for H-Y-zeolite as a commercial sample was about 76%. Later, the same authors showed that FAU-type zeolites exhibited similar conversion of oleic acid to that reported for H-Y-zeolite [60], while adding of Co-Ni-Pt to the FAU-type zeolites increased its activity for biodiesel synthesis in the same procedure to achieve 89% and 93% for continuous and batch reactors, respectively [61].…”
Section: Zeolite-catalyzed Biodiesel Production By Esterification Reamentioning
confidence: 56%
“…In the context of environmental sustainability, heterogeneous catalysts such as ion-exchange resins [4], zeolites [5], ionic liquids [6,7], fly ash cenospheres [8], enzymes [9], Brønsted acids [10,11], and Lewis acids [12,13] were investigated. Apart from these reports, studies related to application of waste materials for the development of efficient catalysts are present in the literature.…”
Section: Introductionmentioning
confidence: 99%